Identifying Wastages and Calculating SMV through Work Sampling Study in Sewing Section (International Journal of Engineering and Computer Science, 2017)
Wastages in the sewing section are very common in garment factory. The sewing workers are engaged in sewing and its associated activities. Beside these, the sewers are provided up to 15% time for allowances due to fatigue, personal needs and machine attention. But sewing operators also spend their time in gossiping, repairing alter, waiting for work and intentionally being idle, which are wastages time. The Standard Minute Value (SMV) is vital in apparel business for target setting, line balancing, man and machine planning. To identify wastages in the sewing section and measure accurate SMV for sewing operations, this work sampling study is carried out in sewing floor. This study is done directly observing 5 sewing operators of collar section by 70 rounds. This study revealed the sewers spend 71.3% time in sewing and its related work and rest of the time in allowances and wastages. This study also calculated SMV of five sewing process. At 95.45% confidence and 5% precision level the measured SMV for c.band hem, c.run stitch, c. top stitch, c.band jnt and c.band t/s are 0.214min, 0.394 mi, 0.379min, 0.503min and 0.319min respectively. The identified wastages and calculated SMV will help the management to take the initiatives to minimize wastage in the sewing section by line balancing, SMV based target setting to the workers and improving supervision.